Pengaruh Substitusi Tepung Kacang Tanah pada Tepung Almon terhadap Karakteristik Kulit Macaron - Safira, Ersha Astria; Ningrumsari, Ida; Khairina, Amila (Jurnal Dimamu, 2024)
Macarons are simple cookies usually made from egg whites, sugar and almond flour. Almonds and almond flour are not produced in Indonesia, and must be imported from abroad, causing the price of almonds and almond flour to be quite expensive in the market. Therefore, in this study, a substitution of peanut flour for almond flour was carried out in making macarons. The purpose of this study was to obtain the right substitution of peanut flour for almond flour to produce the best macaron skin characteristics in terms of moisture content, protein content, fat content, expandability and organoleptic. The research was conducted at the Chemistry Laboratory and Food Processing Laboratory of the Faculty of Agriculture, Ma'soem University and the Chemistry Laboratory of the Bakti Asih Analyst College from February to July 2023. Using the experimental method of Randomized Group Design (RAK) consisting of 6 treatments and 4 repetitions. The treatments were groundnut flour substitution of 0%, 10%, 20%, 30%, 40% and 50% in almond flour by 100%, 90%, 80%, 70%, 60% and 50%. The analysis in this study included water content, protein content, fat content and swelling power as well as organoleptic tests in the form of color, aroma, taste, and appearance of the resulting macaron. The results showed that treatment D (30:70) produced the best macaron characteristics, this determination was based on the level of preference for aroma 4.25 (like), texture 4.30 (like), and taste 4.41 (like). The chemical content of treatment D (30:70) is in the form of water content of (2.89%), protein content of (5.16%) and fat content of (18.54%) as well as growth capacity of (30.02%).